The Impact of Financial Inclusion on MSME Growth in Developing Countries: A Regional Comparative Study - Ida Ayu Putu Megawati; Made Ratih Nurmalasari; Putu Putri Prawitasari; Ni Putu Ari Krismajayanti; Ni Nengah Rupadi Kertiriasih (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the impact of financial inclusion on MSME growth in Bali, Indonesia, and Malaysia. Using Structural Equation Modeling (SEM), the study examines the relationship between financial inclusion, measured by access to financial services, financial literacy, and government policies, and MSME growth, measured by revenue, number of employees, and business expansion. The results show that financial inclusion positively impacts MSME growth in both countries, with a greater effect in Malaysia. In Bali, although financial inclusion has a positive effect, the impact is smaller due to lower financial literacy and limited access to financial services. In Malaysia, more advanced financial inclusion policies and broader fintech access contribute significantly to MSME growth. This study suggests that to foster MSME growth, more structured financial inclusion policies, as well as improving financial literacy and access to financial services, should be a primary focus